(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The elderberry plant (Sambucus nigra) is an excellent resource for many essential nutrients,including protein, free and conjugated forms of amino acids, unsaturated fatty acids, fibre fractions,vitamins, antioxidants, and minerals. Elderberry has been found to contain a number of bioactivecompounds, including the polyphenols anthocyanins, flavonols, phenolic acids, proanthocyanidins,terpenes, and lectins. Elderberry has been utilised in the treatment of a wide variety of illnesses andconditions in traditional medicine. Antioxidant-potential chemicals called polyphenols are responsiblefor elderberry’s therapeutic benefits. Beneficial effects on blood pressure, glycaemia, immune systemstimulation, antitumor potential, increase in the activity of antioxidant enzymes in the blood plasma(including glutathione), and reduction in uric acid levels are just a few examples of the ways in whichthese substances can significantly alter the progression of disease processes.